The effect of vitamin D on the development and function of skeletal muscle - Alliband, Kathryn (2024)
Vitamin D deficiency is a major public health concern affecting around 15% of adults in the UK. Pregnant women have been identified as a sub-group with increased risk of deficiency, with around 20-40% of pregnant women being vitamin D deficient. Currently in the UK, vitamin D supplementation advice for pregnant women is the same as for the general adult population (10µg/day), with no pregnancy specific recommendations, despite pregnant women being an at-risk group. This is a concern for the fetus considering that cord blood contains around 80% of maternal vitamin D levels, therefore infants born to vitamin D deficient mothers are also likely to be vitamin D deficient. Vitamin D is essential for many developmental processes within the fetus including myogenesis, the development of skeletal muscle. The research within this thesis aimed to investigate the effects of vitamin D deficiency on myogenesis and offspring health and establish a mechanism behind these effects. To do this, the current literature was systematically reviewed, in vitro experiments to investigate the effects of vitamin D on myogenesis were carried out and an in vivo study was carried out to investigate the impact of maternal vitamin D deficiency on offspring health. The first research article systematically reviewed twelve studies looking at effects of vitamin D on myogenesis in vitro. It was found that vitamin D inhibited proliferation and increased myotube size, but effects on myogenic regulatory factor and myosin heavy chain expression were unclear. This systematic review revealed problems with variability between studies, particularly in terms of day of measurement, and highlighted the need for time course data within the literature. The second research paper carried out an eight-day differentiation time course in C2C12 cells (a muscle cell line), measuring at six time points, with four concentrations of active vitamin D, spanning physiological range. Similarly to the systematic review, it was found that active vitamin D inhibited proliferation and increased myotube size, but also that active vitamin D resulted in an earlier increase in expression of myogenin and the myosin heavy chain isoforms, showing that vitamin D causes cells to move through differentiation more quickly. Additionally, a vitamin D response element was identified on the myogenin promoter, and the vitamin D receptor was shown to bind to this, via ChIP assay, showing that one of the mechanisms behind the effects of vitamin D on myogenesis is the ability of the vitamin D receptor to bind directly to the myogenin promoter and increase transcription. The third research paper investigated the impact of maternal and infant vitamin D deficiency on offspring health using mice as an in vivo model. Vitamin D deficiency during pregnancy, lactation and infancy was found to affect male offspring to a greater extent than females causing stunted growth of whole-body weight and tissue weights and reduced muscle strength. However, in both male and female offspring, vitamin D deficiency caused insulin resistance and a reduction in physical activity. Overall, the work in this thesis shows clear effects of vitamin D on myogenesis and a negative impact of maternal and infant vitamin D deficiency on offspring health. This highlights the importance of future work needed in this area to give pregnancy specific vitamin D supplementation guidelines and to try to tackle the global issue of vitamin D deficiency during pregnancy.